The Executive Mechanism of Rastin Profit and Loss Sharing (PLS) Banking - Bidabad, Bijan; Allahyarifard, Mahmoud (Indian Journal of Finance and Banking, 2019)
Despite the interest of bankers for using Profit and Loss Sharing (PLS)[1] banking for the last decades, it has not prevailed yet executively. The existence of different definitions of Riba, absence of appropriate operational, supervisory, and managing mechanism on PLS are some reasons that haven’t allowed this kind of banking to be practiced yet. Here, we are going to introduce a practical method for Profit and Loss Sharing (PLS) banking to overcome these problems. In this bank, the basis for determination of interest rate of loans is real economy return rate. The bank operates as an intermediary, who gets commission fee, collects saving resources and as an attorney or legal representative of the depositor, allocates them to investment projects, and supervises the detailed operation of the contractor. The yields of the investment will transfer to resources owners who are depositors whatever profit or losses.The PLS banking is a banking system with newly defined instruments of Mosharaka and Pazireh that not only stabilizes the financial and economic markets by preventing the banks, loanees /entrepreneurs and design, construction and contractor sectors in the economy from bankruptcy during crisis periods and volatile markets, but also makes the banks as an international firm which perform similar jobs as stock exchange markets for transactions of PLS products certificates through a secondary certificate market on virtual internet space. Depositors will earn more stabilized benefits too.In this designed method, a trustee (Amin) is a unit who supervise the contractor/entrepreneur operations on behalf of the bank for being honesty in carrying out the project, controlling on executive operations along with announced programs, resources allocation manner, and auditing financial statements.PLS banking will use new financial instruments and innovations such as Mosharaka (partnership) Certificates for projects with specific ends and Pazireh (Subscripted) Certificates for endless (productive) projects. Establishing of secondary exchange market for the transaction of certificates, and various insurance services will play important roles for activating and increasing the efficiency of newly established virtual markets.All of the activities in this method will be done on the basis of compiled instructions. The framework and the organization of the PLS banking have been analyzed in forms of required committees, units, and departments tailored for this type of Non-Usury Bank (NubankCo.) definition. JEL:L86 ,L87 ,G21 ,G24 [1] - This invention has been protected by US patent law under the application number: US 12/588,188